Postoperative neurocognitive disorders in the elderly: how can we stop the harm? A literature review - Ma, Ling; Jasem, Huthaifa Jasem; Gu, Wan Jun; Zeng, Qi; Wang, Xin; Liu, Xu Dan (Frontiers in Medicine, 2025)
Postoperative neurocognitive disorders (PND) represent a significant challenge affecting patients undergoing surgical procedures, particularly in the elderly population. These disorders can lead to profound impairments in cognitive function, impacting memory, attention, and overall quality of life. Despite ongoing research efforts to identify risk factors and improve management strategies, PND remains underdiagnosed and poorly understood, complicating postoperative recovery and rehabilitation. This review aims to explore the recent advancement in the literature about PND, focusing on the underlying mechanisms, risk factors, and potential therapeutic approaches. We highlight recent advancements in the understanding of neuroinflammation, and it is implications for novel therapies to prevent PND. By synthesizing the latest research, we hope to provide insights that could lead to improved outcomes for patients at risk for PND and foster a shift towards more effective preventive measures in such population.